IMPROVING STUDENTS SPEAKING ABILITY BY USING STORY TELLING TECHNIQUES AT THE TENTH GRADE OF SMA NEGERI 1 LUAHAGUNDRE MANIAMOLO - Siti Hardayanti Wau (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
This research aimed at improving students’ speaking ability by using Storytelling technique. This research was as kind of classroom action research (CAR). This research was carried out in the tenth grade of SMA Negeri 1 Luahagundre Maniamolo with 30 students’ test. The data were analyzed by using qualitative and quantitative analysis to describe the students’ improvement in speaking ability. It showed that before conducting the research, the percentage of the students who can achieved the MCC was only 30%. The students problem there are having low motivation to learn, lack of confidence, they are unmotivated during teaching learning process, the researcher concludes that most of the students’ problem are in the technique of teaching. In collecting data the researcher using observation and test.Then after conducting the result, It can be seen from the students’ result in two cycles of research, where in the cycle I was 37%, or 63% were failed. while in the cycle II it was 80%, whereas 20% were failed. The total score gained in this cycle was 1.939 with the average score was 65. Thus, it can be stated that the students problem in speaking is solved by using story telling technique. Story telling is one of teaching that can be used to improve the students’ speaking. For the Students, English teacher in general suggested should be highly motivated to know a lot of vocabulary and use them in practicing their speaking, and to use of storytelling technique is significantly improving the students’ speaking ability